2018
DOI: 10.1016/j.jbusvent.2018.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurial orientation and innovation in family SMEs: Unveiling the (actual) impact of the Board of Directors

Abstract: Drawing on stewardship and resource dependence theories, we examine how the board of directors (BoD) influences the link between entrepreneurial orientation (EO) and ambidextrous innovation in small and medium sized family firms (family SMEs). Our analysis of 230 Spanish family SMEs shows that family involvement in the BoD has a negative effect on their ability to turn EO into innovation. Moreover, we show that the BoD's strategic involvement in service and control tasks and the provision of knowledge and skil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
181
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 216 publications
(190 citation statements)
references
References 111 publications
(222 reference statements)
5
181
1
3
Order By: Relevance
“…For instance, the recent Arzubiaga et al . 's () study shows that the functioning of the board in terms of its strategic involvement in service and control tasks, the provision of knowledge and skills, and the intensity of board activity has an important effect on the FFs’ ability to turn entrepreneurial orientation into innovation.…”
Section: Where Should We Go? Integrative View and Research Avenuesmentioning
confidence: 99%
“…For instance, the recent Arzubiaga et al . 's () study shows that the functioning of the board in terms of its strategic involvement in service and control tasks, the provision of knowledge and skills, and the intensity of board activity has an important effect on the FFs’ ability to turn entrepreneurial orientation into innovation.…”
Section: Where Should We Go? Integrative View and Research Avenuesmentioning
confidence: 99%
“…Prior research has demonstrated that product innovation is crucial for the survival and prosperity of family firms across generations (e.g., De Massis, Frattini, et al, 2016) and family firm research has often referred to the important role of next‐generation CEOs (i.e., successors) to innovate the products of family firms (e.g., Kraiczy et al, ). Although predecessors constitute important stakeholders in family firms and typically remain involved in postsuccession decision‐making, for instance, through their board retention (Ahrens et al, ; Arzubiaga et al, ; Mitchell et al, ), the current literature has paid scarce attention to their role for product innovation postsuccession so far.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent research has also shown that former family firm CEOs (i.e., predecessors) often remain active in the firm, for instance, through occupying board positions (Mitchell et al, 2009;Quigley and Hambrick, 2012), which allows them to be "able to stay involved and influential in ways that predecessors in nonfamily firms cannot" (Mitchell et al, 2009(Mitchell et al, , p. 1209. Given the influential role of boards in family firms (Arzubiaga, Kotlar, De Massis, Maseda, and Iturralde, 2018), they can thus still significantly influence the decision-making processes and outcomes of family firms (Mitchell et al, 2009;Sharma, Chrisman, and Chua, 2003), including (product) innovation (Hauck and Prügl, 2015;Woodfield and Husted, 2017). While the role of successors for (product) innovation has received significant attention in the family firm literature (e.g., Kraiczy et al, 2015), the role of predecessors in this regard, despite their high importance, has so far been largely overlooked by researchers.…”
Section: Practitioner Pointsmentioning
confidence: 99%
“…In other words, board capital is a combination of the human and social capital of the directors (Haynes & Hillman, 2010). Though extensively investigated in corporate governance studies, the resent researches on boards' role in small firms have attracted considerable attention of scholars (Arzubiaga et al, 2018). Moreover, some scholars extended the definition of top management teams of SMEs by including the members of boards (Nielsen, 2010).…”
Section: Theoretical Background On Board Capitalmentioning
confidence: 99%